(untitled) (Web of Teachers: Inderscience Research, 2023)
The article provides information about the main form of educational work, which is a lesson. The quality and effectiveness of the lesson are related to the structural and methodological aspects of the lesson, which play a huge role in equipping students with knowledge, skills and abilities and contribute to the development of their cognitive powers and abilities. “A lesson is a more or less completed segment, or “cell,” of the pedagogical process. All its sides are reflected in it, like the sun in a drop of water.”